PENGARUH SUBSITUSI KAOLIN TORAGET TERHADAP GIPSUM UNTUK PROFIL DENGAN BAHAN PENGISI SERAT SABUT KELAPA - Doly P Silaban; Petrus Patandung (Balai Riset Dan Standardisasi Industri Manado, 2019)
The effect of substituting Toraget kaolien on gypsum for profile with coconut fiber fiber filler material has been carried out. The aim of the study was to determine the effect of substitution of kaolien toraget and gypsum for profiles with coconut fiber fiber fillers.The research method used a simple Completely Randomized Design (RAL) experiment with a substitution variation of Toraget kaolien and gypsum with constant coconut fiber with a treatment consisting of: A=0:1 (kaolien 0 g and gypsum 3000 g); B=1:9 (kaolien 300 g and 2700 g gypsum); C=3:7 (kaolien 900 g and gypsum 2100 g); D=1:1 (kaolien 1500 and gypsum 1500 g); E=7:3 (kaolien 2100 g and gypsum 900 g); F=9:1 (kaolin 2700 g and 300 g gypsum); G=1:0 (kaolien 3000 g and gypsum 0 g), each treatment was added 10 g of coconut fiber (b / b), and the data was analyzed descriptively. The research was repeated 2 (two) times. The results showed that: the contents of weight were 1.21-1.28%, water absorption was 20.92-53%, flexural strength of 2.10-4.06 kg / cm², hardening time was 0.35-1.49 hours and conditions in general, it can be perfectly printed unless treatment F is imperfect and cracked, and treatment G that uses kaolien 1 part and zero parts of gypsum material does not form a profile and does not tumble and harden. The best results were obtained in treatment D with a ratio that is the ratio of kaolien and gypsum 1:1 or 1500 g kaolien and 1500 g gypsum and treatment E with a ratio of 7:3 namely kaolin 2100 g and gypsum 900 g because it can use balanced kaolien and gypsum and formed a perfect profile and no cracks and meet the profile requirements.Keywords: coconut fiber, gypsum, Kaolien